New species of Pseudachorutes (Collembola: Neanuridae) from Northeastern Algeria - Zoughailech, Abdelmalek; Hamra-Kroua, Salah; Deharveng, Louis (Zootaxa, 2016)
Three new species of Pseudachorutes are described from the Collo massif in northeastern Algeria, all three with morphological features unique or rare in the genus. P. deficiens sp. nov. lacks chaeta E on the labium, a character only retrieved in P. ouatilouensis Najt & Weiner, 1997 from New Caledonia, from which it differs by the presence of chaeta a2 on Th. II and of chaeta M on tibiotarsus. P. octosensillatus sp. nov. is the only species of the genus that have 8 S-chaetae on Ant IV. P. labiatus sp. nov. has 3 x-papillae on the labium, like P. cf. indiana Christiansen & Bellinger, 1980 from Alaska, from which it differs by the presence of chaeta a2 on Th. II and a lower number of vesicles in PAO (5–6 vs 10–14).